HUBUNGAN KARAKTERISTIK IBU DAN LAMA PEMBERIAN ASI EKSKLUSIF DENGAN PENYAKIT INFEKSI DAN STATUS GIZI BAYI USIA 1 – 6 BULAN - PERTIWI, ARIES DIAN; WIRAWANNI, YEKTI (JNH (Journal of Nutrition and Health), 2014)
Background :  Exclusive breastfeeding related to infection and nutritional status of infant. Mothers are represent people who care taken of infant as exclusive breastfeeding. The factors which influence mother to breastfeeding are education, knowledge and mother?s occupation. The  aim of this study to know correlation between mother?s characteristic include education, knowledge and mother?s occupation with duration of exclusive breastfeeding, and to know correlation between duration of exclusive breastfeeding with infection and nutritional status 1-6 months old infants, and also to know correlation between infection frequency and duration of infection with nutritional status 1 -6 months old infants.Design :  This study was an observational with cross sectional design. Samples were infant ages 1-6 months at the work area of Bugangan in East Semarang's public health center, for criteria that samples had not exclusive breastfeeding and samples lived together with the respondent. The respondents were the biological mother of the samples. Minimally samples were 40 infants, using simple random sampling. The data of education, knowledge, mother?s occupation , duration of exclusive and infection collected by interview with respondent. The data of nutritional status of infant was refered to t he index of weight by age (W/A) compared to standart of Z-score WHO NCHS. The programe of SPSS version 11,5 was used to analyze of data. Rank Spearman's was used to examine its correlation.Result :  More than a half of mother's education and knoeledge level was good category. Most of mothers (65 %) didn't work. Most of duration of exclusive breastfeeding was relatively short time  (1,6 ± 1,12 months)  , so that the samples inclined for suffering the infection and this would influence the nutritional status.  There were not any correlation between mother's education (r= 0,194 ; p= 0,232), mother's knowledge (r= 0,156 ; p= 0,337) and mother?s occupation (r= 0,077 ; p= 0,635) with duration exclusive breastfeeding. There were any correlation between duration exclusive breastfeeding with infection frequency  (r= -0,376 ; p= 0,017) and duration of infection (r= -0,486 ; p= 0,001). There was correlation between duration exclusive breastfeeding with nutritional status (r= 0,321 ; p= 0,043). There were correlation between infection frequency (r=  -0.413 ; p=0,008) and duration of infection (r= -0,341 ; p=0,031) with nutritional status.Conclution :  Mother's education, knowledge and occupation were not correlation with duration exclusive brestfeeding. The  longer exclusive breastfeeding the lower for a chance of infection occurrence. Infants whose gets longer exclusive breastfeeding have better nutritional status.Recomand :  To increase the knowledge about the exclusive breastfeeding, infection and nutritional status. And also important to do study about the factors which influence exclusive breastfeeding such as mother's psychology, social economy, environment, media information, and also mother's and infants health condition.Keyword : exclusive breastfeeding, nutritional status, infection, mother?s characteristic. AbstrakLatar belakang : Pemberian ASI eksklusif berhubungan dengan penyakit infeksi dan status gizi. Ibu  merupakan orang yang paling berpengaruh dalam pengasuhan anak termasuk pemberian ASI. Faktor yang mempengaruhi pemberia ASI eksklusif antara lain pendidikan, pengetahuan dan pekerjaan ibu. Penelitian ini bertujuan untuk mengetahui hubungan antara karakteristik ibu meliputi pendidikan, pengetahuan dan pekerjaan ibu dengan lama pemberian ASI eksklusif, mengetahui hubungan lama pemberian ASI eksklusif dengan penyakit infeksi dan status gizi bayi usia 1-6 bulan.0Metode :  Penelitian ini merupakan penelitian observasional dengan desain cross sectional.  Sampel adalah bayi usia 1  ?  6 bulan diwilayah kerja Puskesmas Bugangan Semarang Timur, dengan kriteria sampel sudah tidak ASI eksklusif dan sampel tinggal serumah dengan responden.  Responden adalah ibu kandung dari sampel.  Besar minimal sampel adalah 40 bayi, menggunakan  sample random sampling. Pengambilan data karakteristik ibu, lama pemberian ASI dan penyakit infeksi dilakukan dengan wawancara kepada responden. Data status gizi ditentukan dengan indeks BB/U (Z-score WHO_NCHS) dimana berat badan diambil dengan cara penimbangan berat badan pada bayi. Analisis data menggunakan program SPSS versi 11,5. Uji yang digunakan untuk menganalisis hubungan 2 variabel menggunakan Rank Spearman?sHasil :  Lebih dari separuh pendidikan dan pengetahuan ibu sudah cukup baik. Sebagian besar ibu (65 %) tidak bekerja. Rata-rata lama pemberian ASI eksklusif relatif pendek (1,6 ± 1,12 bulan), sehingga sampel cenderung mengalami penyakit infeksi yang akan mempengaruhi status gizi. Tidak ada hubungan  pendidikan ibu (r= 0,194 ; p= 0,232), pengetahuan ibu (r= 0,156 ; p= 0,337) dan pekerjaan ibu (r= 0,077 ; p= 0,635) dengan lama pemberian ASI.  Ada hubungan lama pemberian ASI eksklusif dengan frekuensi kejadian sakit (r=  -0,376 ; p= 0,017) dan lama kejadian sakit (r=  -486 ; p= 0,001). Ada hubungan lama pemberian ASI eksklusif status gizi (r= 0,321 ; p= 0,043). Ada hubungan frekuensi sakit (r= -0,413 ; p= 0,008) dan lama kejadian sakit (r= -0,341; p= 0,031) dengan status gizi.Kesimpulan : Pendidikan, pengetahuan dan pekerjaan ibu tidak berhubungan dengan lama pemberian ASI eksklusif. Semakin lama pemberian ASI eksklusif semakin rendah kemungkinan terjadinya penyakit infeksi. Bayi yang lebih lama diberi ASI eksklusif mempunyai status gizi yang lebih baik.Saran :  Meningkatkan pemahaman ibu tentang pemberian ASI eksklusif, penyakit infeksi dan status gizi serta perlu dilakukan penelitian tentang faktor-faktor lain yang mempengaruhi pemberian ASI eksklusif seperti  faktor psikologi ibu, sosial ekonomi, lingkunan dan media informasi serta keadaan kesehatan ibu dan bayi.Kata kunci : ASI eksklusif, status gizi, penyakit infeksi dan karakteristik ibu.